43.4k views
0 votes
Solve for x: x^2 + 6√3 x – 9 = 0

User Ryland
by
5.5k points

1 Answer

2 votes

Explanation:

use this equation :

if , ax² + bx + c = 0


x \: = \frac{ - b \: ( + )/( ) \sqrt{ {b}^(2) - 4ac} \: }{2a}

so here, a = 1

b = 6√3

c = -9

let's use the formula .......


x \: = \: \frac{ - 6 √(3) \frac{ + }{} √(36 * 3 - 4(1)( - 9)) }{2(1)}


x \: = \: \frac{ - 6 √(3) \frac{ + }{} √(108 \: + 36) }{2}


x \: = \: \frac{ - 6 √(3) \frac{ + }{} √(144) }{2}


x \: = \: \frac{ - 6 √(3) \frac{ + }{} 12 }{2}


x \: = \: ( - 6 √(3) + 12 )/(2)

OR .......


x \: = \: ( - 6 √(3) - 12 )/(2)

so , X = -3√3 +6 ............ or

X = -3√3 -6 ............

User Rohit Dhawan
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.